We don’t make the News, we just report it: Television Journalism and Narratives of Trauma - Marguerite Moritz; Theresa Crapanzano (Miscelánea: A Journal of English and American Studies, 2010)
While the need to know is the raison d 'être of the journalists, the need to deny is perhaps less obvious but also pervasive, starting with the frequent need to deny their own agency, as our title suggests. In this paper, we take as examples some of the most heavily produced and reported trauma stories of the last decade to illustrate the competing needs of knowing and denying knowledge. These include the 9-11 terror attacks of 2001, the devastation of New Orleans in the aftermath of Hurricane Katrina in 2005, and the school shooting massacre at Virginia Tech University in 2007. The focus is on US journalism because it is a highly influential model providing English language content used around the globe and because it draws heavily on established narrative conventions in both literature and film. Our analysis demonstrates that journalistic needs for knowledge and denial are both cultural and structural and the implications of this on collective and personal memory of traumas are profound.